Rekonstruksi Strategi Misi Gereja di Era Revolusi Industri 4.0 - Yohanes Alfrid Aliano; Eko Armada Riyanto (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Abstract. The authors place the focus of this study on the reconstruction of the strategy of the Church's missionary work by involving the active role of Catholics in the era of the industrial revolution 4.0. The so fast changing times require the Church to be able to see, interpret, evaluate and strengthen the basis of the Church's mission in the light of the faith, hope and love of Jesus Christ by involving all Catholic people. The method used in this study is a literature study in the perspective of Pope Benedict XVI's messages. Through this study, it is understood that in the midst of this sophisticated and modern industrial era, the missionary work of the Church must still place love as the basis of its mission, while at the same time following the currents of modernity. The mission of the Church is a call to work for all believers to fulfill the Great Commission of Jesus Christ.Abstrak. Penulis meletakkan fokus studi ini pada rekonstruksi strategi karya misi Gereja dengan melibatkan peran aktif umat Katolik di era revolusi industri 4.0. Perubahan zaman yang begitu cepat menuntut Gereja untuk mampu melihat, memaknai, mengevaluasi serta memperkokoh dasar karya misi Gereja dalam terang iman, harapan dan kasih Yesus Kristus dengan melibatkan seluruh umat. Metode yang digunakan dalam kajian ini adalah studi pustaka dalam perspektif pesan-pesan Paus Benediktus XVI. Melalui kajian ini diperoleh pemahaman bahwa di tengah era industri yang canggih dan modern ini, karya misi Gereja harus tetap menempatkan kasih sebagai dasar misinya, dengan sekaligus mengikuti arus modernitas. Misi Gereja adalah merupakan panggilan untuk berkarya bagi seluruh umat dalam rangka memenuhi Amanat Agung Yesus Kristus.